Penetapan kadar flavonoid total ekstrak kayu kuning dari daerah Samarkilang Aceh Tengah dengan berbagai konsentrasi etanol menggunakan metode spektrofotometri visible - Afrizani, Afrizani; Daulay, Anny Sartika; Ridwanto, Ridwanto; Rahman, Fathur (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The yellow wood sampled was taken from the Samarkilang area of Central Aceh. The use of yellow wood plants as herbal medicinal ingredients. The chemical compounds contained in Yellow Wood are alkaloids, phenolics, flavonoids, saponins, and tannins. Phenolic compounds and flavonoids have activity as antioxidants. The purpose of this study was to determine the chemical compounds contained in the ethanol extract and to determine the total flavanoid value of the ethanol extract of the yellow wood (Arcangelisia flava (L.) Merr). This research method is an experimental method which includes processing plant materials, making 50%, 70%, and 96% ethanol extracts. Examination of characterization, phytochemical screening and determination of total flavonoid content of the ethanol extract of Kayu kuning using the Uv-Vis spectrophotometry method. Yellow wood extract was prepared by maceration method using various ethanol concentrations of 50%, 70% and 96% the extract obtained was concentrated with a rotary evaporator. Furthermore, the determination of total flavonoid levels was carried out using the Uv-Vis spectrophotometry method. The results of the phytochemical screening on the ethanol extract of Kayu kuning contained groups of chemical compounds such as alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. Determination of total flavonoid content was carried out by determining the maximum wavelength of quercetin, operating time, measuring the quercetin calibration curve and calculating total flavonoid content using the Uv-Vis spectrophotometry method. The results of determining total flavanoid levels in ethanol solvent extract with a concentration of 50% 0,96882 ± 0,2157 mgQE/g, in ethanol solvent extract with a concentration of 70% was 2,6693 ± 11,7041 mgQE/g, and in ethanol solvent extract with a concentration of 96 % is 3,838 ± 1,3036 mgQE/g.